Analisis Perbandingan Kinerja Keuangan PT Alam Karya Unggul Tbk dan PT Kedaung Indah Can Tbk - Nurillah, Nurillah; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the comparison of financial performance between PT Alam Karya Unggul Tbk and PT Kedaung Indah Can Tbk as measured by liquidity and profitability ratios. The liquidity ratio is proxied by the Current Ratio (CR), while the profitability ratio is proxied by Return on Assets (ROA). This research uses a quantitative method with a comparative approach. The data used are secondary data in the form of annual financial statements of both companies during the period 2015–2024, obtained from the official websites of the companies. The sampling technique used is purposive sampling.The data analysis techniques include financial ratio analysis, normality test (Shapiro-Wilk), homogeneity test (Levene Statistic), and hypothesis testing using ANOVA. The results show that descriptively, the Current Ratio (CR) of both companies is in the good to very good category, while Return on Assets (ROA) tends to fluctuate and remains relatively low. The normality test indicates that the data are normally distributed, and the homogeneity test shows that the data are homogeneous.Based on the ANOVA test results, the significance values are greater than 0.05 for both CR and ROA variables, indicating that there is no significant difference in financial performance between PT Alam Karya Unggul Tbk and PT Kedaung Indah Can Tbk. This study is expected to contribute to academics and practitioners in understanding financial performance analysis based on financial ratios.